Military jet aircraft 300 of the world's greatest military aircraft - Sharpe, Michael (Amber Books Ltd, 2018)
"Features 300 of the most important attack, multi-role, and other military jets flown since World War II, including the Messerschmitt Me 262, Mikoyan-Gurevich, MiG-21, Dassault Mirage, and Northrop Grumman B-2 Spirit. Full dimensions, weights, powerplant and armament details provided in metric and imperial for each aircraft. Expert text explains each aircraft's development and service history. Includes 300 profile artworks."